Protection of electricity distribution networks - Gers, Juan M. (Institution of Electrical Engineers, 2011)
Combining a theoretical background with examples and exercises, this book allows the reader to easily follow requirements for high quality electrical service in utilities and industrial facilities around the world.
Previous edition: 2004.
Keywords: Electric power systems -- Protection.; Electric power distribution.; Electric power transmission.; elektronické knihy; electronic books